PENGARUH PENGETAHUAN TERHADAP MINAT MASYARAKAT DALAM KEPESERTAAN BPJS KESEHATAN DI INDONESIA - Sri Nurul Kuraini (Jurnal Admmirasi, 2021)
Efforts to encourage public participation in order to achieve Universal Health Coverage (UHC) means that all Indonesian citizens must be registered as JKN participants. However, during the five years that the JKN program has been running, not all Indonesians have been protected by JKN. This can be seen from the data on the number of BPJS Health participants throughout Indonesia, reaching 719,528 people. The phenomenon seen in the field is that BPJS Kesehatan has not been optimal in increasing the number of JKN participants in Indonesia in 2020. Data from the Ministry of Home Affairs Population and Civil Registration Service for 2020 shows that the total population in Indonesia in 2020 was 268,583,016. soul. This shows that the BPJS membership coverage is still low when compared to the total population , meaning that there are still 46,147,297 people who have not registered as BPJS Kesehatan participants. This study aims to determine the effect of knowledge on public interest in BPJS Health membership. This type of research is quantitative with a cross sectional design . The population was 222,435,719 people. Samples were drawn by accidental sampling, namely as many as 100 people. Data analysis used univariate and bivariate analysis methods. Relationship analysis will be carried out using cross tabulation with the chi square test . The results showed that there was an effect of knowledge (p = 0.020 ) with people's interest in participating in BPJS Kesehatan. The conclusion of this study is getting better knowledge of someone about BPJS, the increasingly high interest in them to become participants BPJS Health, as well as vice versa increasingly less good knowledge of someone about BPJS, then getting a low interest in them to become participants BPJS.